AN ANALYSIS FACTOR THROUGH KAISER-MEYER- OLKIN: DISCLOSING AUDIT TENURE IN BANKING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE 2019 – 2022 - Shabrina Tri Asti Nasution; Devi Ayu Putri; Thezar Fiqih Hidayat Hasibuan (SEAN Institute, 2023)
The Indonesia Stock Exchange requires companies to submit annual financial reports. The purpose of this study is to reveal further the factors of a company's tenure audit on the company's financial statement reporting. Several indicators were used to assess this research, including (a) the length of relationship between companies in the banking sector and the number of years of inspection; (b) the number of years since the audit partner was audited; (c) number of partner auditor offices; (d) the period during which the audit firm changed auditors; and (e) the duration of the auditor's engagement. This study used a quantitative method with secondary data and then the data was analyzed using the Kaiser-Meyer-Olkin (KMO) dimension reduction with IBM SPSS 27 for windows.